Climate change effects on plant disease: genomes to ecosystems. - Dendy, S.P.; Frank, E.E.; Rouse, M.N.; Travers, S.E.; Garrett, Karen A. (My University, 2006)
Research in the effects of climate change on plant disease continues to be limited, but some striking progress has been made. At the genomic level, advances in technologies for the high-throughput analysis of gene expression have made it possible to begin discriminating responses to different biotic and abiotic stressors and potential trade-offs in responses. At the scale of the individual plant, enough experiments have been performed to begin synthesizing the effects of climate variables on infection rates, though pathosystemspecific characteristics make synthesis challenging. Models of plant disease have now been developed to incorporate more sophisticated climate predictions. At the population level, the adaptive potential of plant and pathogen populations may prove to be one of the most important predictors of the magnitude of climate change effects. Ecosystem ecologists are now addressing the role of plant disease in ecosystem processes and the challenge of scaling up from individual infection probabilities to epidemics and broader impacts.
Citation: Garrett, K., . . . & Travers, S. (2006). Climate Change Effects on Plant Disease: Genomes to Ecosystems. Annual Review of Phytopathology, 44(1), 489-509. https://doi.org/10.1146/annurev.phyto.44.070505.143420
Keywords: Climate variability; Disease ecology; Ecological genomics; Epidemiology; Global warming